2022
DOI: 10.1155/2022/5268706
|View full text |Cite
|
Sign up to set email alerts
|

C3-Epimer of 25-Hydroxyvitamin D3 as a Superior Marker for Predicting the Severity of Chronic Kidney Disease in Rheumatoid Arthritis Patients

Abstract: Objective. 25-hydroxyvitamin D3 (25[OH]D3) is involved in oxidative stress regulation by upregulating the expression of antioxidant genes except for mineral homeostasis physiological role. C3-epimer of 25(OH)D3 (C3-epi-25[OH]D3) is a form of vitamin D metabolite with low bioaffinity in vivo, but little is known about the relationship between C3-epi-25(OH)D3 and diseases. This study was aimed at investigating the relationship between C3-epi-25(OH)D3 and the severity of chronic kidney disease (CKD) in patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…In addition, C3-epimer of 25(OH)D 3 (C3-epi-25(OH)D 3 ), a vitamin D metabolite from 25(OH)D 3 through 3β to 3α isomerization transformation, can also affect the amount of bioactive vitamin D conversion [7]. Recent studies have shown that 25(OH)D and its relevant compounds are associated with many diseases, including cancers, kidney, infectious, and autoimmune diseases [8,9]. These findings suggest that vitamin D might play a role in calcium homeostasis, immune regulation, anti-bacterial, and anti-inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, C3-epimer of 25(OH)D 3 (C3-epi-25(OH)D 3 ), a vitamin D metabolite from 25(OH)D 3 through 3β to 3α isomerization transformation, can also affect the amount of bioactive vitamin D conversion [7]. Recent studies have shown that 25(OH)D and its relevant compounds are associated with many diseases, including cancers, kidney, infectious, and autoimmune diseases [8,9]. These findings suggest that vitamin D might play a role in calcium homeostasis, immune regulation, anti-bacterial, and anti-inflammation.…”
Section: Introductionmentioning
confidence: 99%